No quick fix in sight over shortage of government doctors - Abd Razak, Dzulkifli (2004)
NOW that it is quiet on the medical front, maybe it is time to redirect our attention to what Mahatma Gandhi said: The number of hospitals is not a sign of health, but of decay. He is probably right because unless there are sick people, we don't need hospitals. And the more hospitals there are, it would be a fair assumption that there are many more "sick" people around. In other words, in order to cope with the increasing number of "sick" people, more hospitals need to be built, which is somewhat an indicator of the "decay". It then follows that more hospitals will need more doctors and, thus, by the same token, this too can be another sign of the "decay".